Reading fluency: how the construct has developed and its relationship to comprehension - Meggiato, Amanda Oliveira (2021)
There are different definitions of reading fluency and, even though there is a growing consensus that reading fluency involves accuracy, automaticity and prosody, the definitions make it unclear whether fluency contributes to comprehension, whether comprehension promotes fluency, or whether the relationship is reciprocal. This integrative review investigates, describes and compares such definitions, aiming to examine how they address the relationship between fluency and comprehension. The results show that when including prosody in the definition of fluency, it is clear that some level of comprehension is necessary for fluent reading, showing a reciprocal relationship between fluency and comprehension. The conclusions emphasize the importance of directing research towards a better refinement and operationalization of the construct. Pedagogical developments are suggested.